Training and Changes in Job Tasks - Marcus Tamm (Institute of Labor Economics (IZA), 2018)
This study investigates the impact of non-formal training on job tasks of workers. The analysis is based on panel data from Germany covering detailed information on tasks performed at work at the level of individual workers. The results indicate that after training workers are more engaged in non-routine interactive tasks than they were before training. Analyses by topic of training reveal considerable heterogeneity in the impact of training on job tasks. In particular, it is "communication and soft skills" training which is associated with more non-routine interactive tasks.
Keywords: J24; J62; O33; 330; returns to education; routinization; job tasks; training